ANALISIS KESALAHAN BERBAHASA TATARAN SEMANTIK DALAM CERITA RAKYAT “LEGENDA KALI SURA” KARYA VIKA ARANAIA - Fatmawati, Meilani; Mulasih, Mulasih (DIALEKTIKA JURNAL PENDIDIKAN BAHASA INDONESIA, 2025)
The purpose of this study is to analyze language errors in the semantic level of folklore “Legenda Kali Sura” by Vika Aranaia in the book Lokakatha from Tanah Jawa. Language in its application is not free from language errors in both spoken and written language. However, language errors tend to occur in written language, especially errors in the interpretation of meaning due to changes from spoken language to written language that occur in literary works, one of which is folklore. Meaning is closely related to the branch of linguistics, namely semantics. Language errors in the field of semantics are symptoms of hypercorrection, symptoms of pleonasm, and improper selection of words or diction. This research uses a qualitative research approach. The data used in the research are words that contain language errors in the semantic level in the folktale “Legenda Kali Sura” by Vika Aranaia. The data source of this research is the folktale “Legenda Kali Sura” by Vika Aranaia, contained in the book Lokakatha dari Tanah Jawa. The data collection technique is reading and note taking technique. Data analysis techniques through three ways, namely data reduction, data presentation, and drawing conclusions. Data validity is done by tringulation techniques of data sources and theories. The results showed that there was 1 data for hyperchoric symptoms, 6 data for pleonasm symptoms, and 5 data for inappropriate word selection or diction. It can be concluded that semantic level language errors still often occur in written language, the factors that cause this to happen are due to ignorance and lack of knowledge related to language rules in the semantic level. Keywords: semantics, hyperclaim, pleonasm, diction, literature